Rapid cloning of genes in hexaploid wheat using cultivar-specific long-range chromosome assembly - Thind, Anupriya Kaur; Wicker, Thomas; Šimková, Hana; Fossati, Dario; Moullet, Odile; Brabant, Cécile; Vrána, Jan; Doležel, Jaroslav; Krattinger, Simon G (Nature biotechnology, 2017)
Cereal crops such as wheat and maize have large repeat-rich genomes that make cloning of individual genes challenging. Moreover, gene order and gene sequences often differ substantially between cultivars of the same crop species. A major bottleneck for gene cloning in cereals is the generation of high-quality sequence information from a cultivar of interest. In order to accelerate gene cloning from any cropping line, we report 'targeted chromosome-based cloning via long-range assembly' (TACCA). TACCA combines lossless genome-complexity reduction via chromosome flow sorting with Chicago long-range linkage to assemble complex genomes. We applied TACCA to produce a high-quality (N50 of 9.76 Mb) de novo chromosome assembly of the wheat line CH Campala Lr22a in only 4 months. Using this assembly we cloned the broad-spectrum Lr22a leaf-rust resistance gene, using molecular marker information and ethyl methanesulfonate (EMS) mutants, and found that Lr22a encodes an intracellular immune receptor homologous to the Arabidopsis thaliana RPM1 protein.
Keywords: jedlá semena; Cloning, Molecular; Genetic Linkage; Triticum; klonování DNA; Genes, Plant; rostlinné geny; pšenice; Edible Grain; genetická vazba; Biotechnology; biotechnologie